Prefrailty subtypes differentially predict 5-year mortality in the functionally independent geriatric population. (March 2023) - Lee, Yu-Shan; Chen, Yi-Ming; Chou, Yin-Yi; Lin, Chu-Sheng; Chen, Jun-Peng; Kuo, Fu-Hsuan; Lin, Cheng-Fu; Lin, Shih-Yi
Highlights: The definition for slowness and weakness were adjusted to the current criteria produced in 2019. The data about frail population was analyzed in the revised manuscript, as well as the prevalence about the each index of Fried criteria. The method for multivariate regression analysis was described in detail. For the relationship about cognitive function, frailty and PF and mortality, more discussion was shown. Abstract: Introduction: Both frailty and prefrailty (PF) are related to mortality. However, there is no consensus about the PF subtypes for prediction of the mortality risk. We aimed to compare the 5-year mortality of functionally independent geriatric outpatients with nonfrailty, different PF subtypes and frailty. Methods: This was a single-center, retrospective cohort study. Community-dwelling older adults who visited the geriatric outpatient clinic in a healthcare institution in Taiwan were enrolled. PF1 was defined based on exhaustion and/or body weight loss whereas PF2 was defined by one or two of the following criteria: weakness, slowness, and low physical activity. Frailty was defined by three or more above criteria. Demographics and results of comprehensive geriatric assessment were compared and Kaplan–Meier survival analysis was used to determine the 5-year survival among the nonfrail, PF1, PF2 and frail groups. Results: Of the 982 participants, the proportion of PF and frailty was high (PF 45.7% and frailty 24.5%). The cumulative 5-year survival rate of the nonfrail group, PF1, PF2 subgroups and frail group was 98.6%, 95.8%, 89.1% and 81.3% respectively. Age, male sex, PF2 subtype and frailty were significantly associated with 5-year mortality [hazard ratio (95% confidence interval) 1.05 (1.01–1.08), 1.96 (1.08–3.57), 5.18 (1.57–17.09), and 6.87 (2.05–23.04), respectively]. Discussion and conclusion: The proportion of PF and frailty was high in old outpatient population with functional independence. PF2 subtypes and frailty could influence the 5-year mortality risk in these participants. Identifying PF2 participants earlier and instituting prompt intervention may be beneficial in older patients.